Quantification of Hepatitis E Virus in Naturally-Contaminated Pig Liver Products - Martin-Latil, Sandra; Hennechart-Collette, Catherine; Delannoy, Sabine; Guillier, Laurent; Fach, Patrick; Perelle, Sylvie (Frontiers in Microbiology, 2016)
Hepatitis E virus (HEV), the cause of self-limiting acute hepatitis in humans, is widespread and endemic in many parts of the world. The foodborne transmission of HEV has become of concern due to the identification of undercooked pork products as a risk factor for infection. Foodborne enteric viruses are conventionally processed by quantitative RT-PCR (RT-qPCR), which gives sensitive and quantitative detection results. Recently, digital PCR (dPCR) has been described as a novel approach to genome quantification with no need for a standard curve. The performance of microfluidic digital RT-PCR (RT-dPCR) was compared to RT-qPCR when detecting HEV in pig liver products. The sensitivity of the RT-dPCR assay was similar to that of RT-qPCR, and quantitative data obtained by both detection methods were not significantly different for almost all samples. This absolute quantification approach may be useful for standardising quantification of HEV in food samples and may be extended to quantifying other human pathogens in food samples.